Behavioral intention and continued adoption of Facebook: An exploratory study of graduate students in Bangladesh during the Covid-19 pandemic - Hossain Md. Motaher; Zahidul Islam K. M.; Masud Abdullah Al; Biswas Sukanta; Hossain Md. Alamgir (Management)
Behavioral intention and continued adoption of Facebook: An exploratory study of graduate students in Bangladesh during the Covid-19 pandemic